Резолюция Экспертного совета «Диагностика и лечение больных со сладжем в желчном пузыре» - V. T. Ivashkin; Alexey V. Okhlobystin; Dmitry S. Bordin; M. F. Osipenko; E. Ya. Seleznyova; Yu. O. Shulpekova; S. R. Abdulkhakov; O. P. Alexseyeva; I. G. Bakulin; L. G. Vologjhanina; V. B. Grinevich; N. V. Bakulina; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of publication. To present the data of Advisory council which took place on August 19, 2016 in Poland (Krakow) with the participation of Adamed Russia company. Summary. Advisory council activity provided the algorithm of diagnosis and treatment of biliary sludge. At detection of gallbladder sludge in a patient with right hypochondrial pain it is necessary to carry out general examination to rule out the other diseases that may be dangerous (neoplastic, acute cholecystitis, pancreatitis). In the absence of other changes, besides biliary sludge, prescription of initial course of hymecromone combined to ursodeoxycholic acid (UDCA) is indicated. In the case of clinical improvement at primary therapy course it is necessary to continue UDCA treatment for 3 months. Primary treatment course that should include combination of hymecromone and UDCA is indicated for those patients with asymptomatic sludge, who have putty-like bile in the gallbladder or bile ducts. In the case over the other forms of asymptomatic sludge usually only diet limitations and follow up (abdominal US every six months) are indicated. At detection of the ultrasound signs, typical for chronic pancreatitis, according to the Cambridge diagnostic criteria, verification of the diagnosis by multidetector computer tomography according to the pancreatic protocol is mandatory. Selective antispasmodic medications (e.g. hymecromone) will be one of the basic pharmaceutical agents in this case, indications to endoscopic treatment should be evaluated, typically - by means of endoscopic ultrasound investigation). Conclusions. At of patient with the biliary sludge selective antispasmodic medications and UDCA should be widely applied, in some cases methods of endoscopic surgery as well.